2010
DOI: 10.1517/13543776.2010.528392
|View full text |Cite
|
Sign up to set email alerts
|

Spiro azepane-oxazolidinones as Kv1.3 potassium channel blockers: WO2010066840

Abstract: This article evaluates a patent application from Solvay Pharmaceuticals, which claims spiro azepaneoxazolidinones as novel blockers of the voltage-gated potassium channel Kv1.3 for the treatment of diabetes, psoriasis, obesity, transplant rejection and T-cell mediated autoimmune diseases such as rheumatoid arthritis and multiple sclerosis. The patent describes a new chemotype of Kv1.3 blockers and thus illustrates the growing interest of the pharmaceutical industry in Kv1.3 as a target of immunosuppression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…PAP‐1, a synthesized compound Kv1.3 selective, suppresses allergic contact dermatitis by reducing IFN‐ γ production from T EM cells . The synthesized spiro azepone‐oxazolidinone is also considered a novel blocker of Kv1.3 channel for the treatment of diabetes, psoriasis, obesity, transplant rejection and T‐cell mediated autoimmune diseases …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAP‐1, a synthesized compound Kv1.3 selective, suppresses allergic contact dermatitis by reducing IFN‐ γ production from T EM cells . The synthesized spiro azepone‐oxazolidinone is also considered a novel blocker of Kv1.3 channel for the treatment of diabetes, psoriasis, obesity, transplant rejection and T‐cell mediated autoimmune diseases …”
Section: Discussionmentioning
confidence: 99%
“…Recently, many important studies have shown that the T EM is associated with autoimmune diseases (e.g. rheumatoid arthritis, multiple sclerosis, lupus systemic erythematosus and type II diabetes) and that the Kv1.3 channel is up‐regulated in these cells …”
Section: Introductionmentioning
confidence: 99%
“…After inducing the rats with diseased conditions, the results revealed that ShK-186-treated animals had significantly fewer affected joints and showed improvement in radiological and histopathological studies ( Beeton et al, 2011 ). In 2008, a company, Solvay Pharmaceuticals, filed a patent for oxazolidinediones-spiro-azepene as a novel blocker of Kv1.3 potassium channels for the treatment of T-cell-regulated autoimmune diseases such as RA ( Wulff, 2010 ). In addition, kaliotoxin is a molecule with Kv1.3 blocking activity and can be used to treat delayed-type hypersensitivity in RA patients ( Beeton et al, 2001 ; Wulff, 2010 ).…”
Section: Potassium Channels As Therapeutic Targets For Ramentioning
confidence: 99%
“…Derivatives of correolide, a pentacyclic natural compound, have been the object of a SAR study [177]. Patent applications seek to protect whole classes of synthetic K V 1.3 blockers, based on an amide [178] or an oxazolidinedione [179] core. Interestingly, PM K V 1.3 is inhibited downstream of ceramide production by acid sphingomyelinase (ASM) [180].…”
Section: Mitochondrial K V Channelsmentioning
confidence: 99%